Evaluating the Child Abuse and Neglect Institute: Does Training Affect Decision‐Making?. (January 2015) - Sicafuse, Lorie L.; Wood, Steve M.; Summers, Alicia; DeVault, Alicia
Abstract Traditionally, training evaluations have focused on participants' satisfaction and self‐reported knowledge gain. The current study uses a different approach to evaluate the Child Abuse and Neglect Institute (CANI), a training program designed to educate judicial officers on best practices in child abuse and neglect cases. CANI participants were asked to review a case scenario and render decisions about the case before and after the trainings. Findings suggest CANI has several positive impacts on judicial decision‐making, including an increased willingness to engage the father, an increased focus on the child, and increased motivation to comply with the Indian Child Welfare Act.